The effect of damping and force application point on the non-linear dynamic behavior of a cracked beam at sub- and super-resonance vibrations - Bovsunovskyy, Anatoly; Surace, C.; Bovsunovsky, Oleg (My University, 2006)
It is shown the relationship between the crack sizes and non-linear resonanses.
Keywords: non-linear resonance; нелинейный резонанс; нелінійний резонанс; closing crack; закрывающаяся трещина; тріщина, що закривається; кафедра машин і апаратів харчових та фармацевтичних виробництв